Assessing the relationship between banking capitalization and sustainable development in Nigeria - Haladu, Alhassan (Society of Scientific Research and Education (SSRE), 2016)
The fact that the banking industry is not a polluted or environmentally sensitive sector does not immune it from its consequences, because as members of the community they equally owe a responsibility to society.Our major aim in this study is to assess the relationship between banks capital structure and sustainable development in Nigeria.While the manufacturing and other environmentally sensitive sectors are expected to contribute positively towards sustainable development, it is also logical that major creditors (banks) to these industries do same. Scarce literature's on the role of service industries on sustainability reporting is what motivated the researcher to investigate the role banks have been playing in promoting sustainable development given the strength of their capital base. Using 75% of banks quoted in the NSE, the variables were regressed to see the difference in the mean within the periods 2010 to 2013. The result from the F-Change test showed that there is no significance relationship between the capital base of banks and their reporting of social and environmental information. The long-term consequences of such action on the economy may depend on future reporting nature, trend and level.Government should therefore, make sustainability disclosure mandatory and encourage quantitative reporting as opposed to qualitative (pictorial) ones, since there are government agencies charged with the responsibility of enforcing social and environmental Acts.If possible a special tax law like the Global Carbon Tax, be enacted to serve as the contribution of banks and other firms towards sustainable development in the country.